FASILITAS BERMAIN JUNGKAT JUNGKIT UNTUK SLB UNTUNG TUAH SAMARINDA - Noor Qalby; Etwin Fibrianie Suprapto (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2021)
Special School is an educational institute who help special needs children to study with special education provided for them. There is one of Special School located in Samarinda City named Untung Tuah Special School. Just like children in general, special needs children in Special Schools need to play too, that is why there are playground in Special Schools in order for children to not feel depressed during their study. But unfortunately, normal playground facility does not have special safety function for special needs children so some them are not able to use the playground equipments. Seesaw train to cooperate, communicate, social interact, and vestibular system or balance so it is suitable for children to train their feet, hand, etc. The purpose of this design is to create seesaw facility that can help children with special needs, especially intellectual disability and physical disability children, so they can play safely dan comfortable with their friends. The design processs used Vinod Goel’s method that covers formulation of the problem, literature review, data analysis, design analysis, alternative design development, and design final result that are technique drawing, 3D Modeling, prototype, and poster. This design produce a playground equipment as seesaw for special needs children especially intellectual disability and physical disability children. This seesaw is expected to be a safe playground equipment and facilitate special needs children to play freely.